Knowledge of Recommended Pesticide usage among Cabbage Growers - Kumar, M. Naveen; Palanisamy, S (Journal of Extension Education, 2018)
This study aimed to access the knowledge level of cabbage growers on recommended pesticide usage practices. It was carried out in two blocks of Krishnagiri district of Tamil Nadu. Krishnagiri district was selected based on maximum acreage under cabbage cultivation. Two blocks viz., Shoolagiri and Hosur were selected considering the area covered under cabbage. A sample of 120 cabbage growers was selected random selected for the study. A well structured interview schedule was used for data collection and collected data were analyzed using appropriate statistical tools. The findings of the study revealed that majority of the cabbage growers had medium to low level of knowledge on recommended pesticides usage.